POTENSI LUMPUR LAPINDO SEBAGAI BAHAN BAKU TAMBAHAN PEMBUATAN BATU BATA - Rofikatul Karimah (Jurnal Gamma, 2010)
The case of the devastating flood of hot mud from gas drilling PT. LAPINDO Brantas inPorong Siring village of Sidoarjo regency of East Java on 29 May 2006 caused tremendous lossimpact. Puddle and a large volume of mudflow an issue as well must be immediately sought a wayto use it. Business of mud matching is the manufacture of building materials, especially materials ofred brick. It is based on UMM Lumpur research Team (2006) that the Lapindo mud can be used asan ingredient brick-making raw because they contain clay. This study aims to gain prototype madeof mud bricks in accordance with the level / class of bricks.This study is an experiment, the experimental design